El diseño digital y lógica mixta - Betancourt Uscátegui, Alvaro (Ingeniería, 2001)
A good design style should be easy to understand and to learn, force the designer to think through the total design before the construction. Mixed logic methodology still meet some resistance and is prefered the positive and negative logics design techniques. Although the technique is older, but the power has not been widely appreciated. The paper presents the basic idea of mixed logic concepts and its utility.